2020
DOI: 10.1590/s1678-3921.pab2020.v55.01900
|View full text |Cite
|
Sign up to set email alerts
|

Techniques to modify cluster architecture and their effect on the viticultural performance of the Sauvignon Blanc cultivar

Abstract: The objective of this work was to evaluate the effect of different techniques to modify grape cluster architecture on the incidence and severity of botrytis bunch rot, as well as on the viticultural performance of the 'Sauvignon Blanc' grapevine (Vitis vinifera). Associated with fungicides, four treatments were tested: control, 30 ppm gibberellic acid sprayed at full bloom, 1,000 ppm prohexadione calcium sprayed at full bloom, and berry thinning at the stage of beginning of berry touch. The experiment was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(36 reference statements)
0
2
0
1
Order By: Relevance
“…Previous studies have demonstrated that GA 3 application at full bloom is more detrimental than at pre‐bloom because it decreases grape yield and bud fertility, and increases the incidence of Botrytis cinerea infection of grape fruit 12,27 . Mundy et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that GA 3 application at full bloom is more detrimental than at pre‐bloom because it decreases grape yield and bud fertility, and increases the incidence of Botrytis cinerea infection of grape fruit 12,27 . Mundy et al .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that GA 3 application at full bloom is more detrimental than at pre-bloom because it decreases grape yield and bud fertility, and increases the incidence of Botrytis cinerea infection of grape fruit. 12,27 Mundy et al found that a high rate of GA 3 application (40 mg L −1 ) reduced blooming in the following reason, 11 and Gao et al recommended applications of GA 3 above 50 mg L −1 to loosen wine grape bunching. 2 In this study, the highest concentration of pre-bloom GA 3 treatment used was 25 mg L −1 .…”
Section: Grape Physicochemical Parametersmentioning
confidence: 99%
“…No entanto, observa-se nessa região condições climáticas também são favoráveis a muitos fungos que podem reduzir significativamente o rendimento e a qualidade da fruta. (DE BEM et al, 2015;BRIGHENTI et al, 2020).…”
Section: Introductionunclassified